SEMARANG DAN SURABAYA DALAM PERSPEKTIF HISTORIS DAN EKONOMI KOTA: SEBUAH PEMIKIRAN HISTORIOGRAFIS - Putri Agus Wijayati (SASDAYA: Gadjah Mada Journal of Humanities, 2017)
This article describes the economic history of the town and its dynamics. As part of the historical reality, urban economics further accentuates its economic elements based on trade, industry and services activities. Of the three factors above, which one actively contributes to growth in urban economic development? Or, among the three, may be intertwined or synergised, which in turn form a support force that can stimulate the economic growth rate of a city. However, is it that simple in explaining the economic history of the town?, because a historical study must also be considerate of changes over time, while when discussed is the economic dimension, then, we are dealing with statistical data used to understand a change in time, as is done by quantitative economic history. This paper takes spatial space in the cities of Surabaya and Semarang as both cities, dominantly influenced by elements of trade, industry and services.